Acervos científicos brasileiros de vertebrados: uma análise crítica no atual contexto de conservação da biodiversidade - Sousa, Eloisa Paula Bispo de (Universidade Federal do Tocantins, 2018)
The purpose of this research was to understand, demonstrate and divulge the importance of biological scientific collections of vertebrates in Brazil, in order to provide an overview of the current situation of these collections, their participation in society for the insertion of values, preservation of culture, formation professional, research and diffusion of knowledge. In order to search for information needed to understand the reality of the country's scientific collections, questionnaires were sent via e-mail to the Institutions, in addition to telephone contact and search of data on its own websites, or platforms for accessing data from online collections. The survey showed 117 representative collections of the 5 classes of vertebrates, linked to 44 Institutions. The size of the collections was specified in number of specimens or lots, species, genera, families, orders, endangered species and type species. About the largest collections in each group were detailed information more specific and pertinent to the understanding of their performance. However, major gaps still exist, mainly related to the dissemination of data on the collections, in addition to internal problems such as lack of financial resources, infrastructure that falls short of actual needs, lack of specialized human resources, among others, but it is believed that this situation can be resolved through active policies and projects of actions that encourage improvements in these aspects. It is hoped that this research served to highlight the importance of these collections, their fundamental role in several areas of knowledge and to alert about their indispensable needs to offer more effective contributions to society.